Press Freedom and Its Relevance to the Theory of People's Sovereignty In the Indonesian Legal Regime - Syafriadi; Santri, Selvi Harvia (Universitas Islam Indonesia, 2025)
Press freedom in Indonesia intersects closely with the doctrine of popular sovereignty, yet its boundaries vis-à-vis state authority remain contested. Adopting a normative-juridical methodology with qualitative descriptive analysis, the research reviews constitutional provisions, statutes, judicial decisions, and scholarly commentary. Findings show that Indonesia’s normative commitment to a free press resonates with Jean-Jacques Rousseau’s concept of popular sovereignty, under which the state may regulate public life without extinguishing civil liberty. Second, despite guarantees in Article 28F of the 1945 Constitution and Law No. 40 of 1999 on the Press, journalists face political intimidation, media-ownership concentration, and insufficient legal protection and conditions that chill independent reporting. Consequently, press freedom functions as a barometer of popular sovereignty; an informed populace can exercise self-government only when information circulates freely, objectively, and responsibly. To bridge the gap between constitutional promise and daily practice, the article recommends amending the Press Law to strengthen newsroom independence, define interference penalties, and expand the Press Council’s authority to enforce ethical standards and safeguard journalists. Such reforms are essential to balancing state regulation with citizens’ right to reliable information and reinforcing Indonesia’s status as a constitutional democracy rooted in the people's sovereignty.